2019
DOI: 10.1089/bioe.2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Changes in Electrical Impedance During Cell-Mediated Mineralization

Abstract: Background: The fundamental electrical properties of bone have been attributed to the organic collagen and the inorganic mineral component; however, contributions of individual components within bone tissue toward the measured electrical properties are not known. In our study, we investigated the electrical properties of cell-mediated mineral deposition process and compared our results with cell-free mineralization. Materials and Methods: Saos-2 cells encapsulated within gelatin methacrylate (GelMA) hydrogels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…13,15 Along these lines, Ramos et al recently demonstrated that electrical impedance (resistance of cells to current flow) is decreased as mineral mass is increased in cell-mediated mineral constructs. 28 Since DPSCs have been shown to have stronger mineralization capacity than BM-MSCs, 29 perhaps, as differentiation occurs, electrical currents conduct more quickly and are sensed more intensely by DPSCs. In addition, another explanation for the observed effects could be differences between MSCs and DPSCs in their intercellular ion distribution and sensitivity to EStim-generated reactive oxygen species (ROS) in the medium (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Along these lines, Ramos et al recently demonstrated that electrical impedance (resistance of cells to current flow) is decreased as mineral mass is increased in cell-mediated mineral constructs. 28 Since DPSCs have been shown to have stronger mineralization capacity than BM-MSCs, 29 perhaps, as differentiation occurs, electrical currents conduct more quickly and are sensed more intensely by DPSCs. In addition, another explanation for the observed effects could be differences between MSCs and DPSCs in their intercellular ion distribution and sensitivity to EStim-generated reactive oxygen species (ROS) in the medium (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Investigations of the deposition of mineral on chip under biomimetic conditions using impedance have so far been limited to measurements at a single frequency and a single timepoint. [29] These measurements do not take full advantage of the benefits of EIS, both in terms of the potential to perform automated time-series measurements due to the noninvasive nature of the technique and in terms of the amount of information that can be obtained from a single measurement by performing a frequency sweep.…”
Section: Introductionmentioning
confidence: 99%
“…Confinement was achieved by overlaying the osteocyte monolayer with a photopolymerizable GelMA matrix. The GelMA matrix was selected because it chemically resembles the native collagenous bone matrix, contains integrin attachment sites that facilitate interaction of the cytoskeleton and matrix through focal adhesions, and is conducive to mineralization by embedded osteoblastic cells as we have shown previously [57][58][59]. Connectivity of the osteocytes can be manipulated by varying the seeding density of the osteocytes.…”
Section: Discussionmentioning
confidence: 99%